Experience of water, sanitation and hygiene (wash) in Nepal, and its relationships with international tourist's health, travel plans and experiences - Bhatta, Ramesh (2021)
ABSTRACT: Background: Tourism is important for the economic growth as well as to alleviate poverty and achieve greater social equity in the country. Annually, tourism sector contributes about 6.7% of total GDP and also support in employment. Nepal has immense resources to attract tourists; however they are influenced by the situation of water, sanitation and hygiene (WASH). Poor WASH provisions are considered risk factors for different diseases that are transmitted through consumption of contaminated water and the faecal-oral route amongst travelers. Consumption of faecally contaminated water or food is associated with a number of food-and water-borne diseases that affect travelers (such as shigellosis, typhoid fever and hepatitis A), and diarrhea is the most frequent illness reported amongst international tourists to developing nations. This study aims to describe the perceptions among international travelers to Nepal regarding access to and experiences of WASH facilities, assess whether these perceptions are associated with self-reported gastrointestinal illnesses (e.g. diarrhoea), and whether and how these factors influence their future travel plans and travel experience. Methods: This is a cross-sectional study and has employed a mixed method (quantitative and qualitative) approach to collect data. Study information was collected from 150 respondents, selected as per convenience of the researcher. The survey tool and interview questionnaire guideline was used, which were tested before collecting study data. The quantitative data was entered into SPSS for descriptive analysis and qualitative data was transcribed through thematic analysis. Results: Out of 150 respondents, majorities were from age group 20-30 yrs and most of them were from Europe. Mostly (80.7%) tourist had visited Nepal to spend their vacation, and 76% of them have travelled together with their family and friends. Study shows that 72.7% of the respondents had poor perception toward the sanitation condition of the place they visited. Similarly, 22.7% of the respondents told that they experienced diarrhea in the past week during the Nepal visit. About 21.4% of the respondents told that the gastrointestinal related symptoms that they faced have affected their travel plan, out of them 88.8% of them have to stop their planned activities and travelling. Despite of poor water, sanitation and hygiene that the tourist had faced in Nepal, still 99.3% of the respondents told that they will recommend their friends and other to visit Nepal due to the various reasons such as; having natural beauty with beautiful mountains and lake, being birthplace of lord Buddha, having good atmosphere, nice and friendly peoples and due to the delicious food that are available at hotels and restaurants. Conclusions: Tourism is taken as an important industry for boosting economic growth of the country. Nepal have potential to attract many more tourists, however there are many aspects related with water sanitation and hygiene that need to be considered for tourism development. Unsafe water, poor sanitation and hygiene have negative impact on the health of tourist as well as it also affect the tourism industry. There has been continuous effort made from governmental as well as non-governmental sector to improve the water and sanitation facilities, however the problem of continuity and sustainability still exist. Hence, for promoting the tourism industry and to increase the number of tourists, it is urgent for the government to focus on improving access to the safe water and basic sanitation facilities throughout the country.